Anesthetic and surgical management of mucoid retention cyst in the vallecular region: An airway challenge - Christina George; Aditya Martin; Narjeet Meena Osahan; Dootika Liddle (Wolters Kluwer Medknow Publications, 2018)
Growth of any kind in the oropharynx poses a threat to the airway especially during anaesthesia. Being aware of the challenges and adequately equipped to handle the situation is the duty of the anesthesiologist. Methods and Material: An eight year old girl diagnosed case of multiple mucous cysts presented to the outpatient department for excision of a lower lip mucous cyst. So an ultrasound was done which revealed a large intramural mucous cyst. After a preanaesthetic checkup she was posted for the excision of the cyst. Results: The girl was posted for Elective surgery and was induced without prior premedication as she had revealed a history of snoring in supine position. After preoxygenating with 100% oxygen, she was induced with Injection Ketamine and Sevoflurane. She started desaturated abruptly so nasal airway and finally # 2.5 LMA was inserted but SpO2 didn't improve. With backup of Ent and paediatric surgeons direct larngoscopy was attempted and #5 ETT was inserted successfully. Following which the huge vallecular cyst was removed.